1995
DOI: 10.1016/0014-5793(95)01102-k
|View full text |Cite
|
Sign up to set email alerts
|

Altered P450 activity associated with direct selection for fungal azole resistance

Abstract: Azole antifungals inhibit CYP51Al-mediated sterol 14c~-demethylation and the mechanism(s) of resistance to such compounds in Ustilago maydis were examined. The inhibition of growth was correlated with the accumulation of the snbstrate, 24-methylene-24,25-dihydrolanosterol (eburicol), and depletion of ergosterol. Mutants overcoming the effect of azole antifungal treatment exhibited a unique phenotype with leaky CYP51A1 activity which was resistant to inhibition. The results demonstrate that alterations at the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Leaky P45051 mutants have been identified as being azoleresistant in other laboratory studies on U. maydis (9) and prompted further study of the mutant enzyme. Alteration of the Thr 315 residue to alanine also subtly disturbed the hemoprotein as indicated by the change in the Soret maximum to 445 nm from 448 nm.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Leaky P45051 mutants have been identified as being azoleresistant in other laboratory studies on U. maydis (9) and prompted further study of the mutant enzyme. Alteration of the Thr 315 residue to alanine also subtly disturbed the hemoprotein as indicated by the change in the Soret maximum to 445 nm from 448 nm.…”
Section: Discussionmentioning
confidence: 97%
“…The development of resistance to fluconazole in Ͼ10% of late stage AIDS patients suffering candidosis has stimulated interest on the mechanisms of resistance and how to diagnose and overcome this problem. It is known for a few isolates of Candida albicans that resistance can occur through phenomena related to decreased accumulation of drug in the cell (5,6), although for other fungi suppressor mechanisms operate that change the 14␣-methylated sterols accumulating under treatment (7,8), and recently leaky P45051 mutants of Ustilago maydis were identified that exhibited resistance, demonstrating altered target site as a mechanism of resistance in a congenic background (9). Previously, a P45051-defective strain, SG1, was observed to be azole-resistant, but such resistance can be attributed to the second defect it has in sterol ⌬ 5,6 -desaturation, which suppresses the effect of a chemical or genetic block at P45051 (10).…”
mentioning
confidence: 98%
“…Several resistance mechanisms have been described in C. albicans [14,151, particularly nonspecific mechanisms such as enhanced efflux of drug involving ATP binding cassettes or major facilitators, responsible for multidrug resistance [ 16-1 81. Also, more specific mechanisms consisting of changes in the binding site [19] or catalytic site [20] on the azole target, amplification or increasing transcription of the P-45ODM gene [16,21,221 [14,27,281. These studies relied on the comparison of two clinical isolates obtained from a unique patient in which the microorganism had become resistant during treatment with fluconazole.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported mechanism of resistance to site-speciWc fungicides is decreased aYnity of the target site for the inhibitor. However, resistance to DMIs caused by decreased aYnity of P45014DM for these fungicides has been rarely observed (Joseph-Horne et al, 1995;Vanden Bossche et al, 1990). In the powdery mildew fungi of grapevine, Erysiphe necator (syn.…”
Section: Introductionmentioning
confidence: 96%